2011
DOI: 10.4297/najms.2011.3268
|View full text |Cite
|
Sign up to set email alerts
|

Royal jelly modulates oxidative stress and tissue injury in gamma irradiated male Wister Albino rats

Abstract: Background:Royal jelly is a nutritive secretion produced by the worker bees, rich in proteins, carbohydrates, vitamins and minerals.Aim:The present study was designed to determine the possible protective effects of royal jelly against radiation induced oxidative stress, hematological, biochemical and histological alterations in male Wister albino rats.Materials and Methods:Male Wister albino rats were exposed to a fractionated dose of gamma radiation (2 Gy every 3 days up to 8 Gy total doses). Royal jelly was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 29 publications
(27 reference statements)
3
33
0
Order By: Relevance
“…These results were also recorded by several authors (Ali and Haggag, 2006;Abdel Mottaal andAbdel Maguid, 2007, Bakhit, 2010 ;Azab et al 2011).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results were also recorded by several authors (Ali and Haggag, 2006;Abdel Mottaal andAbdel Maguid, 2007, Bakhit, 2010 ;Azab et al 2011).…”
Section: Discussionsupporting
confidence: 81%
“…Abnormal structures of cardiac muscles were found as ill-defined shape, necrotic, pyknotic nuclei, sever dilated, widened and inflammated capillaries in endomysium ( Azab et al 2011). …”
Section: Introductionmentioning
confidence: 98%
“…The present study showed the improvement in the tested blood parameters as erythrocytes, hemoglobin, leukocytes, platelets and the mean value of packed cell volume (PCV), mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH) indicates that honey and royal jelly administration prevented blood cell damage by maintaining the integrity of cells. Administration of royal jelly to rats ameliorated the effect of radiation that induced oxidative stress and hematological alterations [56].…”
Section: Discussionmentioning
confidence: 98%
“…Honey and royal jelly have a protective role against many drugs, wherever [55] the honey protective effects on organs through the improvement in the hematological parameters (RBCs, WBCs and Platelets) because of decreased lipopolysaccharide in rats. Honey is reported to attenuate the hematological, effects induced by gentamicin [56,45]. Natural honey significantly (P<0.05) restored Hb content, RBC, PCV, platelet and WBC close to control values in wistar albino rats fed hydrocarbon contaminated diets [57].…”
Section: Discussionmentioning
confidence: 99%
“…RJ has been reported to modulate tissue injury and oxidative stress in rats. [13,14] A study has reported the antioxidant property of RJ by preparing enzyme hydrolysates which are having much higher antioxidant activity. [15] Further anti-inflammatory dose-dependent effect of RJ against formalin in rat hind paw was observed.…”
Section: Original Articlementioning
confidence: 99%